Proses Penciptaan Karya Tari Kreasi B Aris Tanda - I Ketut Sutapa; I Putu Gede Bagus Restu Pratama Wiwaha; Gusti Ayu Ketut Suandewi (Departement of Mathematics Education, 2023)
Baris Tanda is a new dance with the theme of heroism about widyadaras. The sign comes from the word tamanwa which means the first dance of Lord Rudra. The Wa Sign in the Kesiman Traditional Village is interpreted as a Sign, one of the properties of Pengarebongan and Sapuh Agung during the Pangilen ceremony at Pura Agung Petilan. The Baris Tanda dance, which is danced by seven male dancers, represents a combination of the Mantra Puja Dynamics and Mudras contained in the Bratha Natyam book. This dashing dance is presented in the form of a group dance with a smoky composition, rows and circles accompanied by Gamelan Semarandana digital music. This newly created dance was created using the Angripta Sesolahan creation method (creating dances) with the planning, nasen, makalin, nelesin, and grain processes. This dance work was created in the framework of the Merdeka Learning-Independence Campus Program, a collaboration between the Indonesian Art Institute and the Pancer Langit Art Studio.